2022
DOI: 10.1111/jocd.14762
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNAs in melanin metabolism: Implications in melanin‐related diseases

Abstract: Background: MicroRNAs (miRNAs) are short single-stranded non-coding RNAs that regulate degradation and expression of messenger RNA (mRNA) and play a wide range of key roles in different biological processes. They mediate different stages of melanocyte differentiation, growth, and apoptosis through a variety of pathways and can mediate melanin production by targeting key enzymes.Aims: This article was aimed to review the role of miRNAs in melanin metabolism and to introduce the role and significance of miRNAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…In contrast to our results, Dong et al found overexpression of miR-137 in their study that targets c-KIT in melanocytes 73 . Overexpression of miR-137 may reduce the expression of Tyrosinase Related Protein 2 (TYRP2) and c-KIT and reduce the increase in melanin production caused by ultraviolet (UV) treatment 74 . It is suggested that miR-137 can inhibit melanogenesis in mouse skin melanocytes by inhibiting the expression of c-KIT and TYRP2 in the SCF/c-KIT signaling pathway 75 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results, Dong et al found overexpression of miR-137 in their study that targets c-KIT in melanocytes 73 . Overexpression of miR-137 may reduce the expression of Tyrosinase Related Protein 2 (TYRP2) and c-KIT and reduce the increase in melanin production caused by ultraviolet (UV) treatment 74 . It is suggested that miR-137 can inhibit melanogenesis in mouse skin melanocytes by inhibiting the expression of c-KIT and TYRP2 in the SCF/c-KIT signaling pathway 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Melanogenesis is the name of the process that produces different types of melanin [ 1 , 2 ]. Although melanin protects skin from the harmful effects of ultraviolet radiation, overproduction results in unwanted complications in the skin, such as freckles, lesions, and discoloration, to name few [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al (2020) analyzed the pathogenic factors and pathogenesis of chloasma from the perspective of traditional Chinese medicine and western medicine, providing theoretical basis for the treatment of chloasma. Zhang et al (2022) discussed the effect and mechanism of miRNA, and analyzed the significance of miRNA in the pathogenesis of chloasma. Chen et al (2020) treated chloasma with Bletilla striata polysaccharide cream and Honghua Xiaoyao tablets.…”
Section: Introductionmentioning
confidence: 99%